(3GdLhgQI GdefjaI aj TQM hUjI CHj MfjaIs - (3GdQhej, MSjf Hf EScfOQ (B,(3fMh (B1084 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdeJhMO HhLhH GdhLhO (B...(3aEfj GSJNJ Gddg JYGdi aj hVY TQM eNJUQ Ydi cJGH GdhUjI GdefShH Edi GdEeGe GdCYXe CHh MfjaI QVj Gddg JYGdi Yfg HYO Cf hbaJ Ydi TQMg ddYdGeI GdCced (B...s
(3BNQgG (B:s
... (3aGFOI ojQhi Cf GdedGFcI bGdJ jGQH h Gf GdSeGA hGdCQV Mjf GeQJgG YUjGe eG cfJ UGfYG HgeG bGd cfJ BeQG OGHI ef OhGHj aJHdYgeG bGdhG jGQH hCjf Jdc GdOGHI bGd aj eQL ef eQhLj cPG aj bUU GdCfHjGA ddKYdHj hGdMeO ddgs
(3bHdg ahGFO (B- (3JGQjN GdJCdja (B( 13 (3LeGO GdBNQ (B1060 (3g` (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\233s
(3EjVGM Gdecfhf (B1\386s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs